MEKANISME GOOD CORPORATE GOVERNANCE DAN DEWAN PENGAWAS SYARIAH PADA KINERJA KEUANGAN PERBANKAN SYARIAH INDONESIA - Anthon Indra Jaya; M Rasuli (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
This study aims to discuss and analyze about how the mechanism internal of good corporate governance such as: Effect of audit committe effectiveness on the performance of sharia banking, Effect of risk monitoring committee effectiveness on sharia banking performance, Effect of remuneration and nomination committee effectiveness on sharia banking performance, and also sharia supervisorsboard effectiveness on sharia banking performance in Indonesian between 2014-2018. The data used in this study are secondary data by measuring the number of meetings taken from each variable. The method used in sample selection is purposive sampling. The number of samples in this study were 12 banks taken from the annual report with 60 samples. The hypothesis test used in this study is the statistical t test. The data analysis technique used in this study is multiple linear analysis using statistical products and service solutions (SPSS) version 20.0. The results of the study showed that the effectiveness of audit committee, risk monitoring committee, nomination and remuneration committee, and sharia supervisory board had a positive effect on the financial performance of sharia banking